2019
DOI: 10.1163/15685411-00003286
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and incidence of plant-parasitic nematodes associated with saffron (Crocus sativus L.) in Morocco and their relationship with soil physicochemical properties

Abstract: SummarySaffron (Crocus sativus) fields in Morocco’s Taliouine and Taznakht regions were surveyed between January and April 2018 to study the diversity and incidence of plant-parasitic nematodes and assess the effects of soil physicochemical properties on the nematodes. Fourteen nematode genera were identified in soil and root samples collected from 66 saffron fields. The most common plant-parasitic nematodes in the Taliouine region were Pratylenchus spp. and Helicotylenchus spp. In the Taznakht region, the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…In this current study, four species of Pratylenchus, viz. P. penetrans, P. thornei, P. neglectus, and P. crenatus were found, which was in agreement with what has been previously reported in organic farming in Germany [13], the United States [63,64], as well as in conventional wheat and saffron cultivations in Morocco [16,60]. Pratylenchus penetrans has a broad host range of more than 400 different plants, as the most damaging species [65].…”
Section: Distribution and Diversity Of Ppn Communities In Some Moroccsupporting
confidence: 89%
See 4 more Smart Citations
“…In this current study, four species of Pratylenchus, viz. P. penetrans, P. thornei, P. neglectus, and P. crenatus were found, which was in agreement with what has been previously reported in organic farming in Germany [13], the United States [63,64], as well as in conventional wheat and saffron cultivations in Morocco [16,60]. Pratylenchus penetrans has a broad host range of more than 400 different plants, as the most damaging species [65].…”
Section: Distribution and Diversity Of Ppn Communities In Some Moroccsupporting
confidence: 89%
“…Helicotylenchus vulgaris was also an important nematode in Southern Morocco, affecting 40.2% of the sampled organic farms with a population density of up to 7 nematodes per 100 cm 3 of soil. In previous studies, H. vulgaris was recorded in around 59% and 30% of the sampled Moroccan saffron fields of Taliouine and Taznakht, respectively [60], and 6.5% of the organically grown vegetable fields in Germany [13]. In another study, Adam et al [14] reported the presence of Helicotylenchus spp.…”
Section: Distribution and Diversity Of Ppn Communities In Some Moroccmentioning
confidence: 96%
See 3 more Smart Citations